Orthodontic management of a young boy with Class I malocclusion with crowding, supernumerary tooth and rotated central incisor: A case report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
This article describe the treatment of a boy of 15 years old, with Class I malocclusion and anterior crowding and rotated upper right central incisor. The patient had thick and fleshy extra labial frenum between upper right central and lateral incisor. The patient had also rotated supernumerary tooth labial to upper right lateral incisor. The patient was treated by extraction of supernumerary tooth and frenectomy followed by derotation of right central incisor with standard edgewise orthodontic therapy.Ban J Orthod & Dentofac Orthop, October 2012; Vol-3, No.1